Expression of peptide fragments from proADM and involvement of mitogen‐activated protein kinase signaling pathways in pulmonary remodeling induced by high pulmonary blood flow. (January 2016) - Li, Wei; Guo, Aili; Wang, Lijuan; Kong, Qingyu; Wang, Rong; Han, Li; Zhao, Cuifen
Abstract: Pulmonary arterial hypertension (PAH) is a life‐threatening disease characterized by progressive pulmonary arterial remodeling and right ventricular failure. Despite recent advances in pathophysiological mechanism exploration and new therapeutic approaches, PAH remains a challenging condition. In this study, we investigated the roles of the peptide fragments from proadrenomedullin (proADM) such as adrenomedullin (ADM), adrenotensin (ADT), and proadrenomedullin N‐terminal 20 peptide (PAMP) during pulmonary remodeling caused by high pulmonary blood flow, and probed the possible involvement of mitogen‐activated protein kinase (MAPK) signal transduction pathways. Sixteen rat models of PAH were artificially established by surgically connecting the left common carotid artery to the external jugular vein. We subcutaneously injected an extracellular signal‐regulated protein kinase (ERK1/2) inhibitor, PD98059, in eight rats, treated another eight rats with an equal volume of saline. Eight rats without connections served as the control group. We observed that mRNA expression levels of ADM, stress‐activated protein kinase (SAPK), and ERK1/2 were significantly elevated in the shunted rats; furthermore, ERK1/2 levels were significantly inhibited by PD98059. Protein levels of ADM, PAMP, p‐SAPK, and p‐ERK1/2 were significantly higher ADT was lower, and p‐ p38 remained unchanged in the rat models compared with the controls. However, the protein expression of both ADM and p‐ERK1/2 was significantly inhibited by PD98059. Our results suggest that levels of ADM, ADT, and PAMP respond to pulmonary remodeling, and that activation of the SAPK and ERK1/2 signaling pathways is involved in pulmonary hypertension and artery remodeling caused by high pulmonary blood flow.